数字经济时代算法风险的刑法规制. - 马天一 (Journal of Xi'an Jiaotong University (Social Sciences), 2025)
In the era of digital economy, algorithm risk brings new challenges to the protection of social public interests and citizens' legitimate rights and interests. China attaches great importance to algorithm legislation, and has created a large number of regulations around algorithm recommendation, algorithm synthesis, algorithm training, algorithm ethical review and other matters. However, the Criminal Law of the People's Republic of China, as the safeguard law and the last law, lacks effective regulation of algorithmic risk, which makes the legal governance of algorithmic risk deficient. Although there are a large number of studies on algorithmic risk regulation in the existing literature, there are few research results on algorithmic governance in criminal law, and there is a problem of insufficient systematization. In fact, in the era of digital economy. algorithmic risk contains multiple levels of infringement of legal interests, algorithmic risk is caused by subjective intention-driven behavior, and other social control means are weak in regulating algorithmic risk. These factors make algorithmic risk accountable in criminal law, and it is necessary to strengthen the regulation research on algorithmic risk in criminal law. Therefore, this paper focuses on the study of the dilemma, governance principle and countermeasures of algorithmic risk in the era of digital economy. The research mainly adopts the combination of literature research method and normative analysis method, and analyzes the function positioning and governance deficiencies of criminal law in the algorithm governance system from the principle of the unity of legal order. In addition, the research is carried out in combination with the latest legislation on algorithms in China and the governance experience involving algorithms at home and abroad, and analyzes the criminal law regulation of algorithm risks from a systematic perspective. It has formed the systematic research results, including the analysis of dilemma performance, the analysis of the cause of dilemma, the analysis of the solution of dilemma and the analysis of the framework of the solution of dilemma. This paper holds that the current criminal law can only regulate the algorithm risk indirectly, and the problems such as fuzzy criminal law application standard in the algorithm application scenario, weak connection between the algorithm supervision order and the criminal law guarantee, and unclear criminal law attribution logic in the algorithm accountability principle all exist objectively. In order to better realize the governance of algorithmic risk in the era of digital economy, we should examine the transformation needs of legal interest theory from the perspective of algorithmic risk, and establish a two-layer legal interest protection principle of algorithmic right legal interest as the blocking layer legal interest and the specific legal interest of crime protection as the substantive layer legal interest. On this basis, typed criminal law regulation should be developed based on algorithm risk scenarios, including refining criminal law regulation combined with application scenarios. strengthening criminal law regulation for criminal use, and prudently using criminal law regulation based on derivative risks. We should carry out systematic criminal law guarantee according to the algorithm supervision order. realize the criminal law absorption of algorithm supervision terms, the criminal law confirmation of algorithm platform responsibility, and the criminal law strengthening of algorithm external supervision. In addition, the principle of algorithmic accountability should be combined with criminal law liability based on causality and subjective aspects respectively, so as to realize the systematic response of criminal law to algorithmic risks in the era of digital economy. The innovations of this paper include the proposal of taking algorithm rights as the main legal interests of criminal law protection in algorithm governance, the further integration of criminal law and algorithm terminology under the principle of unity of legal order. and the theoretical solutions of criminal law in the fields of algorithm supervision. algorithm platform responsibility. algorithm causality and so on. These research results provide a solid foundation for the next step of criminal law theory and practice.